Persepsi Penutur ‘Baghandu’ sebagai Tradisi Lisan di Kabupaten Kampar - Tiara Zulva (Journal on Education, 2023)
This study aims to get to know more about the 'Baghandu' oral tradition in the Kampar Regency area. Baghandu is a tradition in Kampar Regency, Riau Province. This art is carried out from generation to generation and is spoken by speakers who do not convey baghandu haphazardly. This study aims to find out how to inspire the storyteller in humming. The research used is a qualitative research type. The techniques used in collecting data in research are observation, interviews, recording and taking notes. The data that has been collected must be reviewed again, namely reading it many times carefully and carefully in the data, marking the data then describing the data, and making conclusions. This data can be obtained from information about the storyteller Baghandu.